4-Trifluoromethyl-(E)-cinnamoyl]-L-4-F-phenylalanine acid exerts its effects on the prevention, post-therapeutic and prolongation of the thrombolytic window in ischemia-reperfusion rats through multiple mechanisms of action. (April 2022) - Feng, Jia-Hao; Hu, Xiao-Long; Lv, Xian-Yu; Hong, Yu; Zhang, Yuan-Hao; long, Huan; Wang, Rong; Wang, Jing-Jin; Xiong, Fei; Wang, Hao
Abstract: Ischemic stroke is one of the leading causes of death and disability worldwide. The severe sequelae caused by ischemic thrombolysis and the narrow time window are now the main clinical challenges. Our previous study has reported 4-Trifluoromethyl-( E )-cinnamoyl]- L -4-F-phenylalanine Acid (AE-18 ) was a promising candidate for Parkinson's Disease. In this study, the preventive and therapeutic effects of AE-18 on focal cerebral ischemia-reperfusion injury and the mechanisms are explored. In oxygen glucose deprivation/reoxygenation (OGD/R)-induced well-differentiated PC12 cells model, AE-18 (10 or 20 μM) can significantly reduce nerve damage when administered before or after molding. In middle cerebral artery occlusion-reperfusion (MCAO/R) rat model, pre-modelling, or post-modelling administration of AE-18 (5 or 10 mg/kg) was effective in reducing neurological damage, decreasing infarct volume and improving motor disturbances. In addition, AE-18 (5 mg/kg) given by intravenous injection immediately after occlusion significantly reduce the infarct volume caused by reperfusion for different durations, indicating that AE-18 could extend the time window of thrombolytic therapy. Further studies demonstrate that AE-18 exerts the effects in the prevention, treatment, and prolongation of the time window of cerebral ischemic injury mainly through inhibiting excitotoxicity and improving BBB permeability, VEGF and BDNF. These results suggest that AE-18 is a good candidate for the treatment of ischemic stroke. Graphical Abstract: ga1 Highlights: This study demonstrates that AE-18 exerted preventive effects against ischemia-reperfusion-induced brain injury. AE-18 relieved cerebral edema by improving ischemia-reperfusion-induced BBB permeability after reperfusion. In the subacute phase after reperfusion, AE-18 showed a therapeutic effect on brain I/R injury by ameliorating neuronal loss. AE-18 prolongs the thrombolytic time window with acute phase I/R injury.